Evaluation of Pleura Efusion Determination by Light’s and Heffner’s Cciteria - Nor Jannah Ali; Ani Kartini; Darmawaty Effendi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
EVALUATION OF PLEURA EFUSION DETERMINATION BY LIGHT’S DAN HEFFNER’S CRITERIANordjannah1, Ani Kartini2, Darmawaty ER 31 Medical Doctor Specialist Education Programe of Clinical Pathology, Faculty of Medicine Hasanuddin University/dr.Wahidin Sudirohusodo Hospital, Makassar2 Department of Clinical Pathology Faculty of Medicine, Hasanuddin University/ Labuang Baji Hospital Makassar3 Department of Clinical Pathology Faculty of Medicine, Hasanuddin University/ Hospital Islam Faisal Hospital Makassar ABSTRACT Background : Pleural effusion is a condition of abnormal pleural fluid accumulation in the pleural cavity due to excessive transudation or exudation. Light’s criteria is used as the standard method to distinguish between exudates and transudates. Some recent studies reported misclassifications so several alternative criteria are developed, one of which is Heffner’s criteria. The purpose of this study was to determine the sensitivity and specificity of Heffner’s criteria in determining the type of pleural effusion.Methods : An observational study with cross sectional method using a pleural effusion fluid sample of patients examined at the Clinical Pathology Laboratory Instalation at Wahidin Sudirohusodo Hospital on July 2018. Total protein, LDH and cholesterol levels were examined in all samples that met the inclusion and exclusion criteria.Results : There were 45 samples of pleural effusion, 30 of which classified as transudate and 15 samples as exudates. Based on clinical diagnosis, the Light’s criteria obtained 3 misclassifications and Heffner’s criteria obtained 2 misclassifications. Based on the data above, the statistical data showed that Light’s criteria has sensitivity of 96,7 % and specificity of 86,7 %. Heffner’s criteria has sensitivity of 100 % and specificity of 86,7 %. Conclusion : Heffner’s criteria offers better sensitivity and specificity than Light’s criteria. Heffner’s criteria can be used as an alternative in determining the type of pleural effusion Keywords: Heffner’s criteria, Light’s criteria, transudate, exudate, pleural effusion